Beyond the epic : the life & films of David Lean - Phillips, Gene D. (University Press of Kentucky, 2006)
Two-time Academy Award winner Sir David Lean (1908-1991) was a prominent director in the world of twentieth-century cinema, responsible for such classics as The Bridge on the River Kwai, Doctor Zhivago, and Lawrence of Arabia. British-born Lean asserted himself in Hollywood as a major artistic voice with his epic storytelling and panoramic depictions of history, but he was also a highly skilled film editor in Great Britain before he became a director who brought an art-house sensibility to big market films. Lean's approach to filmmaking was far different from that of his contemporaries. He car.